1998
DOI: 10.1253/jcj.62.571
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Rebound Phenomenon Related To Intermittent Nitroglycerin Therapy for the Prevention of Nitrate Tolerance

Abstract: but there was no difference between the control and the intermittent application phases. However, in the intermittent removal phase, the cGMP level before sublingual NTG, the %cGMP and the %VV were unchanged, but the VV before sublingual NTG was significantly lower than in the control phase. Plasma renin activity and the plasma level of angiotensin II were significantly increased in the continuous phase, the intermittent application phase, and the intermittent removal phase. In conclusion, intermittent transde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although we can not prove causality, we fear that NTG may have been a contributing factor because the cardiac event rate was significantly higher in the study group than in the general population undergoing the same surgery. A few studies have shown that abrupt cessation of NTG may cause a 'rebound phenomenon' of myocardial ischemia after patch removal (25)(26)(27). In the Second Transdermal Intermittent Dosing Evaluation Study (TIDES II) (27), patients suffered more ischemic episodes during patch-off hours after use of intermittent transdermal NTG.…”
Section: Discussionmentioning
confidence: 99%
“…Although we can not prove causality, we fear that NTG may have been a contributing factor because the cardiac event rate was significantly higher in the study group than in the general population undergoing the same surgery. A few studies have shown that abrupt cessation of NTG may cause a 'rebound phenomenon' of myocardial ischemia after patch removal (25)(26)(27). In the Second Transdermal Intermittent Dosing Evaluation Study (TIDES II) (27), patients suffered more ischemic episodes during patch-off hours after use of intermittent transdermal NTG.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo Ang II treatment for 7 days in rats increased the activity and expression of NOX, leading to increased O 2 •− production, eNOS uncoupling, impaired NO/cGMP signaling, and endothelial dysfunction (Mollnau et al, 2002). In healthy human subjects, plasma Ang II increased after continuous transdermal NTG application (Watanabe et al, 1998), and in rabbits, 3 days continuous treatment with NTG patches resulted in an increase in Ang II type 1 (AT 1 ) receptor mRNA expression, and a marked increase in constrictions to Ang I and II (Kurz et al, 1999). These findings led the last group of investigators to conclude “a pathophysiological role for angiotensin II..... in the development of nitrate tolerance”.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma Ang II levels remained elevated despite avoidance of tolerance via intermittent dosing (Watanabe et al, 1998), suggesting that the Ang II response might be a result of hemodynamic counter-regulation (so-called pseudo-tolerance). An obligatory involvement of the endothelium in nitrate tolerance was indicated (Kurz et al, 1999), but several investigators have found that vascular NTG tolerance can be induced in the absence of the endothelium, and cross-tolerance between NTG and acetylcholine was not observed (Stewart et al, 1987; Mulsch et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies primarily focused on inflammatory and oxidative stress pathways in response to traffic noise exposure in the context of CVD development (for review see [22,23,131]), while human data linking noise exposure to measures such as telomere length and DNA methylation are generally lacking. Evidence on the association between traffic noise exposure and biological aging mainly arises from animal studies [154][155][156][157][158][159]. Indirect evidence on the role of noise exposure in biological aging is given by human studies demonstrating oxidative DNA damage, a correlate of altered DNA methylation and gene expression, in subjects exposed to occupational [160,161] and traffic noise [114].…”
Section: Human Evidence On the Association Between (Traffic) Noise Exposure And Biomarkers Of Agingmentioning
confidence: 99%